CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Adaptation to climate change in irrigated agriculture in Uzbekistan* - Shukhrat Mukhamedjanov; Azamat Mukhomedjanov; Rustam Sagdullaev; Nazokat Khasanova (Irrigation and Drainage, 2021)
In recent years, climate change in Central Asia, especially in Uzbekistan, has resulted in sharp alternation of dry and wet years. In such conditions, agriculture has turned into the most vulnerable sector. Agricultural producers have not been able to adapt to such variations of climatic conditions. Traditional irrigation approaches and agronomic operations are becoming unacceptable against the background of severe droughts or heavy rains. Moreover, intra‐annual distribution of precipitation and air temperature has changed. Especially in agriculture, increased rainfall in spring and summer and decreased rainfall in autumn and winter has had a negative impact. In 2013, the Global Water Partnership initiated the Water, Climate, and Development Programme for Caucasus and Central Asia. In the Fergana Valley of Uzbekistan, a project was implemented to study the possibility of agriculture adaptation to climate change within the framework of this programme. This article presents an analysis of long‐term data received from 1960 to 2014 on air temperature and precipitation. As a result of these studies, it has been determined that we can forecast the current year's weather conditions if we find a similar year in recent years. For the Fergana Valley of Uzbekistan, it has been established that we have a stable spring, when winter is cold with heavy precipitation, and we have a cold spring and summer with high precipitation, when we have a warm winter with low precipitation. Past experience has shown that the use of water for irrigation, taking into account climatic conditions, has a significant impact on reducing irrigation water and increasing crop yields.

The role of antibiotics and antibiotic resistance in nature - Rustam I. Aminov (Environmental Microbiology, 2009)
Summary Investigations of antibiotic resistance from an environmental prospective shed new light on a problem that was traditionally confined to a subset of clinically relevant antibiotic‐resistant bacterial pathogens. It is clear that the environmental microbiota, even in apparently antibiotic‐free environments, possess an enormous number and diversity of antibiotic resistance genes, some of which are very similar to the genes circulating in pathogenic microbiota. It is difficult to explain the role of antibiotics and antibiotic resistance in natural environments from an anthropocentric point of view, which is focused on clinical aspects such as the efficiency of antibiotics in clearing infections and pathogens that are resistant to antibiotic treatment. A broader overview of the role of antibiotics and antibiotic resistance in nature from the evolutionary and ecological prospective suggests that antibiotics have evolved as another way of intra‐ and inter‐domain communication in various ecosystems. This signalling by non‐clinical concentrations of antibiotics in the environment results in adaptive phenotypic and genotypic responses of microbiota and other members of the community. Understanding the complex picture of evolution and ecology of antibiotics and antibiotic resistance may help to understand the processes leading to the emergence and dissemination of antibiotic resistance and also help to control it, at least in relation to the newer antibiotics now entering clinical practice.

Desulfotomaculum genus‐ and subgenus‐specific 16S rRNA hybridization probes for environmental studies - Krassimira R. Hristova; Margit Mau; Dandan Zheng; Rustam I. Aminov; Roderick I. Mackie; H. Rex Gaskins; Lutgarde Raskin (Environmental Microbiology, 2000)
Based on comparative analysis of 16S rRNA sequences and the recently established phylogeny of the genus Desulfotomaculum , a set of phylogenetically nested hybridization probes was developed and characterized. A genus‐specific probe targets all known Desulfotomaculum species (with the exception of Desulfotomaculum acetoxidans ), and five specific probes target subclusters within the Desulfotomaculum genus. The dissociation temperature of each probe was determined experimentally. Probe specificities were verified through hybridizations with pure culture rRNA isolated from a wide variety of target and non‐target organisms and through an evaluation of probe ‘nesting’ using samples obtained from four different environments. Fixation and hybridization conditions for fluorescence in situ hybridizations were also optimized. The probes were used in quantitative membrane hybridizations to determine the abundance of Desulfotomaculum species in thermophilic anaerobic digesters, in soil, in human faeces and in pig colon samples. Desulfotomaculum rRNA accounted for 0.3–2.1% of the total rRNA in the digesters, 2.6–6.6% in soil, 1.5–3.3% in human faeces and 2.5–6.2% in pig colon samples.